Amaryllidaceae-type alkaloids as anticancer hit/leads, targeting multidrug resistant cancer cells - Sancha, Shirley (2023)
Multidrug resistance (MDR) is the major challenge in cancer chemotherapy. The main objective of this study was to find new effective anticancer compounds, from two species of Amaryllidaceae family to target MDR cancer cells. The phytochemical study of the methanol extract of the bulbs of Narcissus bulbocodium L. subsp. obesus gave rise to the Amaryllidaceae-type alkaloid tazettine (1) and β-sitosterol (3). In addition, from the methanol extract of the flowers, the alkamide N-trans-feroulyl-tyramine (2) and the steroids β-sitosterol (3), β-sitosterol-O-β-D-glucoside (4), β-sitostenone (5), and ergosterol peroxide (6) were also isolated. In turn, the study of the methanol extract of the bulbs and flowers of Pancratium maritimum L. yielded 8-O-demethyl-2α-hydroxyhomolycorine (8), a new Amaryllidaceae alkaloid, along with the known alkaloids lycorine (7), 2α-10bα-dihydroxy-9-O-demethylhomolycorine (9), 8-O-demethylhomolycorine (10), hippeastrine (11), haemanthamine (12), haemanthidine (13), epigalanthamine (14) and 11β-hydroxygalanthamine (15) and the phenolic compound 4,6-dimethoxy-2- hydroxy acetophenone (16). Aiming at generating a small library of Amaryllidaceae-type alkaloids, the chemical derivatization of lycorine (7), 2α-10bα-dihydroxy-9-O-demethylhomolycorine (9), and haemanthidine (13), isolated in large amount from P. maritimum, allowed the preparation of seventy-five derivatives. In this way, the chemical reaction of lycorine (7) with carbonyldiimidazole and different aromatic and aliphatic amines, afforded thirty-one new mono- and di-carbamates (7.1–7.31). Furthermore, cleavage of ring D with ethyl chloroformate of the diacetylated lycorine derivative (7.32) gave rise to compounds 7.34–7.44, bearing carbamate and amine functions. In addition, lycorine was treated with strong base resulting in Hofman elimination with the opening of ring D and aromatization of ring C to afford the derivative 7.45. Acylation of compound 9 provided the diester 9.1 and the monoesters 9.2–9.5. Oxidation of haemanthidine (13) yielded compound 13.1, while the reaction with acetic anhydride gave rise to the diester 13.2. Moreover, reaction of haemanthidine with aliphatic and aromatic halides originated the conversion into tazettine (1) and tazettine-, and pretazettine-type N- and O-alkylated derivatives (1.1– 1.24). The chemical structures of the compounds were established from their physical and spectroscopic data, namely IR, 1D- ( 1H NMR, 13C NMR) and 2D-NMR (COSY, HMBC, HMQC, and NOESY) experiments and MS. The antiproliferative effect of compounds 1-3, 5-16 was evaluated by the sulforhodamine B assay against the triple-negative breast cancer cell lines MDA-MB-231 and MDA-MB-468, breast cancer cells MCF-7, and the non-malignant fibroblast (HFF-1) and breast (MCF12A) cell lines. The alkaloids 7, 9, 12, and 13 showed significant growth inhibitory effects against all breast cancer cell lines IC50 (0.73- 16.3 µM). The homolycorine-type alkaloid 9 was selected for further investigation of the mechanism of action in MDA-MB-231 cells. In the annexin-V assay, compound 9 increased cell death by apoptosis, which was substantiated, in western blot analyses, by the increased expression of the pro-apoptotic protein Bax, and the decreased expression of the anti-apoptotic protein Bcl-xL. Consistently, it further stimulated mitochondrial reactive oxygen species (ROS) generation. The antiproliferative effect of compound 9 was also associated with G2/M cell cycle arrest, which was supported by an increase in the p21 protein expression levels. In MDA-MB-231 cells, compound 9 also exhibited synergistic effects with conventional chemotherapeutic drugs such as etoposide. The anticancer potential of the alkaloids 1–3 and 5–16 was also assessed in HCT116 colon cancer cells. The cytotoxicity of the compounds was evaluated by the MTS metabolism. Compounds 7, 12, and 13 exhibited the most potent cytotoxic activity with IC50 values of 2.07, 4.98, and 5.90 µM, respectively. The induced inhibition of proliferation of HCT116 cells by compound 12 was associated with G1 phase arrest, while compounds 7 and 13 induced G2/M cell cycle arrest. Lycorine (7) and its carbamate derivatives 7.1–7.31 were evaluated as MDR reversers, through functional and chemosensitivity assays, in resistant human colon adenocarcinoma cancer cells (COLO 320), overexpressing P-glycoprotein (P-gp). Significant inhibition of P-gp efflux activity was observed for the di-carbamates, mainly those containing aromatic substituents, at non-cytotoxic concentrations. Compound 7.4, bearing a benzyl substituent, and compounds 7.8 and 7.24, with phenethyl moieties, were among the most active, exhibiting strong inhibition at 2 µM, being more active than verapamil at a 10-fold higher concentration. In drug combination assays, most compounds were able to synergize doxorubicin. Moreover, some derivatives showed a selective antiproliferative effect toward resistant cells, having a collateral sensitivity effect. In the ATPase assay, some selected compounds (7.1, 7.4, 7.8, 7.18, 7.24, and 7.25) behaved as inhibitors. The effects of alkaloids 7, 9, and 13 and their derivatives (7.32–7.45, 9.1–9.5, 13.1, 13.2, and 1, 1.1–1.24) on the reversal of drug resistance were evaluated in resistant human ovarian carcinoma (HOC/ADR) cells, overexpressing P-gp. The derivatives 7.32–7.45, and 9.1–9.5 were not cytotoxic or showed moderate/weak cytotoxicity, however, lycorine (7) exhibited strong cytotoxicity (IC50 values of 1.2- 2.5 µM). In combination assays, most of the compounds synergized with the anticancer drug doxorubicin. Compounds 7.34, 7.35, 7.38–7.43, bearing both carbamate and aromatic amine moieties, showed the highest sensitization rate, reducing the dose of doxorubicin 5–35 times, thus highlighting their potential to reverse drug resistance in combination chemotherapy. Selected compounds (7.33–7.36, 7.38–7.43, and 9.5) that re-sensitize resistant cancer cells were further evaluated as P-gp inhibitors. Compound 7.40, with a para-methoxy-N-methylbenzylamine moiety, was the strongest inhibitor. In the ATPase assay, compounds 7.38–7.40 and 7.42 behaved as verapamil, suggesting competitive inhibition of P-gp. Chemosensitivity and functional assays were also employed to assess the MDR reversal of haemanthidine (13), tazettine (1), and its derivatives (1.1–1.24) in resistant human ovarian carcinoma cells. Compounds 1.4, 1.14, 1.18, and 1.23, bearing aromatic moieties with methoxy and bromide substituents, exhibited the highest sensitization rate (up to 30-fold). Compounds 1.4, 1.12, and 1.13, sharing phenethyl moieties, with methoxy and bromide substituents, exhibited the strongest P-gp inhibitory activity P-glycoprotein. In conclusion, several Amaryllidaceae-type alkaloids of both natural origin and obtained by derivatization are promising potential lead structures as MDR reversers. Keywords: Multidrug resistance; Amaryllidaceae-type alkaloids; Apoptosis induction; Cell cycle arrest, P-glycoprotein.